Multi-level sales management in Vietnam - Cao, Xuan Nhat (ĐHQG, 2016)
Research aims and tasks: - Showing correctness, legality and development potential of multi-level sales in the current situation in Vietnam. - Finding out difficulties in managing this new kind of business for Vietnam - Giving management suggestions so that business activities can run effectively and exploit its positive sides. Topic’s structure: Except preface, conclusion, list of supplementary documents, main contents of the topic are divided into 3 chapters: - Chapter 1 : general introduction about multi- level sales - Chapter 2 : situation of multi-level sales in Vietnam - Chapter 3 : Some management suggestions Research achievements: - Finding a comprehensive and good look on theis new kind of business in Vietnam - Analysing, evaluating and showing the situation of multi- level sales in Vietnam now - Suggesting and explaining solutions about managing this new kind of business effectively.